SEHAT DAN FIT DIUSIA TUA DENGAN BEROLAHRAGA - Oce Wiriawan, ; Agus Hariyanto, ; Amrozi Khamidi, (Arena, 2010)
Old age is the accumulation of conditions and diseases of aging phenomenon is indeed a condition of Physio-biological reduction phase for the time limit set by Allah Almighty who created us. Fitness is not just physical fitness, it mirrors the passionate quality of work life (active life). Therefore, fitness fitness concerns are also psychological and social. Let us wait for ages, without accompanied by a "disease" which is basically because of our own behavior.